[Formula Presented]-boson interferometry and generalized Wigner function - Zhang, Q. H.; Padula, Sandra S. (American Physical Society (APS), 2004)
Bose-Einstein correlations of two identically charged [Formula Presented] bosons are derived considering these particles to be confined in finite volumes. Boundary effects on single [Formula Presented]-boson spectrum are also studied. We illustrate the effects on the spectrum and on the two-[Formula Presented]-boson correlation function by means of two toy models. We also derive a generalized expression for the Wigner function depending on the deformation parameter [Formula Presented], which is reduced to its original functional form in the limit of [Formula Presented]. © 2004 The American Physical Society.